Different gonadotropin releasing hormone agonist doses for the final oocyte maturation in high-responder patients undergoing in vitro fertilization/intra-cytoplasmic sperm injection - Emre Goksan Pabuccu; Recai Pabuccu; Gamze Sinem Caglar; Banu Yilmaz; Asli Yarci (Wolters Kluwer Medknow Publications, 2015)
Context: Efficacy of gonadotropin releasing hormone agonists (GnRH-a) for ovulation in high-responders. Aims: The aim of the current study is to compare the impact of different GnRH-a doses for the final oocyte maturation on cycle outcomes and ovarian hyperstimulation syndrome (OHSS) rates in high-responder patients undergoing ovarian stimulation. Settings And Designs: Electronic medical records of a private in vitro fertilization center, a retrospective analysis. Subjects and Methods: A total of 77 high-responder cases were detected receiving GnRH-a. Group I consisted of 38 patients who received 1 mg of agonist and Group II consisted of 39 patients who received 2 mg of agonist. Statistical Analysis: In order to compare groups, Student's t-test, Mann-Whitney U-test, Pearson's Chi-square test or Fisher's exact test were used where appropriate. A P < 0.05 was considered as statistically significant. Result: Number of retrieved oocytes (17.5 vs. 15.0, P = 0.510), implantation rates (46% vs. 55.1%, P = 0.419) and clinical pregnancy rates (42.1% vs. 38.5%, P = 0.744) were similar among groups. There were no mild or severe OHSS cases detected in Group I. Only 1 mild OHSS case was detected in Group II. Conclusion: A volume of 1 or 2 mg leuprolide acetate yields similar outcomes when used for the final oocyte maturation in high-responder patients.